(untitled) (The International Journal of Educational Sciences and Arts, 2024)
This study aimed to reveal the effect of using the flipped classroom strategy in developing the cognitive growth of the food unit among kindergarten children. The experimental method was used with a semi-experimental design, one-group, on a research sample consisting of (22) children from the third level from the Kindergarten Teachers Training Center in the city of Jeddah. The two researchers prepared a pre-post cognitive test for the food unit. The results of the study revealed that there are statistically significant differences between the mean scores of the children of the experimental group in the pre and post applications to measure the growth of basic and higher thinking skills among kindergarten children in the food unit, and the differences came in favor of the post application. The study also recommends training and encouraging kindergarten and early childhood teachers to use the flipped classroom strategy in the educational process.